PERSEPSI MASYARAKAT MENGENAI DAMPAK PENGANGGURAN TERHADAP KENAKALAN REMAJA DI DESA BANGKO LESTARI KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Kurniawan, Budi; Zahirman, Zahirman; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study is entitled "Community Perceptions Regarding the Impact of Unemployment on Juvenile Delinquency in Bangko Lestari Village, Bangko Pusako District, Rokan Hilir Regency". The formulation of the problem in this study is how the public perception of the impact of unemployment on juvenile delinquency in Bangko Lestari Village, Bangko Pusako District, Rokan Hilir Regency. The purpose of this study was to determine how people's perceptions about the effects of unemployment on juvenile delinquency in Bangko Lestari Village, Bangko Pusako District, Rokan Hilir Regency. The population of this research is the whole community of Bangko Lestari Village, Bangko Pusako District, Rokan Hilir Regency. While the sample of this study amounted to 100 respondents. Data collection techniques are observation, questionnaire, interview, library and documentation. Data analysis techniques using quantitative descriptive method. The conclusion of this study is the percentage of answers to strongly agree (SS) by 7% plus the answers to agree (S) by 41% so that it gets 48% results in the range of "Poor", so that the Community Perception About the Impact of Unemployment on Juvenile Delinquency in Bangko Lestari Village Bangko Pusako District, Rokan Hilir Regency is "Not Good"Key Words: Community Perception, Unemployment, Juvenile Delinquency